The Interior Designing of Lawu Resort Hotel with Tirta Intanpari Batik Theme in Tawangmangu - Wahyu Tri Widiyanto; Putri Sekar Hapsari (Institut Seni Indonesia Surakarta, 2020)
The increasing number of tourists visiting Tawangmangu tourist attraction, Central Java, and yet insufficient lodging facilities are some of what is behind the interior designing of Lawu Resort Hotel. Lawu Resort Hotel is a lodge with facilities to accommodate tourist activities. The design theme is intanpari tirta batik design with a contemporary style, meanwhile the design goal is to present an interior that follows current times advancement but still concerns on the culture. The design method adopted the stages of the Pamudji Suptandar design process with an outline of the process consisting of input, synthesis and output. The scope of work includes a lobby, restaurant, coffee lounge and guest room. The design results are in the form of a design proposal, which includes design concepts, work drawings, material schemes and animation.